'The truest form of patriotism': Pacifist feminism in Britain, 1870-1902 - Brown, Heloise (Manchester University Press, 2003)
This fascinating book explores the pervasive influence of pacifism on Victorian feminism. Drawing on previously unused source material, it provides an account of Victorian women who campaigned for peace and the many feminists who incorporated pacifist ideas into their writing on women and women's work. It explores feminists' ideas about the role of women within the empire, their eligibility for citizenship and their ability to act as moral guardians in public life. Brown shows that such ideas made use - in varying ways - of gendered understandings of the role of force and the relevance of arbitration and other pacifist strategies. 'The truest for of patriotism' examines the work of a wide range of individuals and organisations, from well-known feminists such as Lydia Becker, Josephine Butler and Millicent Garrett Fawcett, to lesser-known figures such as the Quaker pacifists Ellen Robinson and Priscilla Peckover. Women's work within male-dominated organisations, such as the Peace Society and the International Arbitration and Peace Association, is covered alongside single-sex organisations, such as the International Council of Women. Also reviewed are the arguments put forward in feminist journals like the Englishwoman's Review and the Women's Penny Paper. Brown uncovers a wide range of pacifist, internationalist and anti-imperialist strands in Victorian feminist thought, focusing on how these ideas developed within the political and organisational context of the time. This book will be of interest to anyone studying nineteenth-century social movements, and essential reading for those with an interest in the history of British feminism.